Active duty and ex-serving military personnel with post-traumatic stress disorder treated with psychological therapies: systematic review and meta-analysis. Issue 1 (31st December 2019) - Kitchiner, Neil J.; Lewis, Catrin; Roberts, Neil P.; Bisson, Jonathan I.
ABSTRACT: Background : Post-traumatic stress disorder (PTSD) is a major cause of morbidity amongst active duty and ex-serving military personnel. In recent years increasing efforts have been made to develop more effective treatments. Objective : To determine which psychological therapies are efficacious in treating active duty and ex-serving military personnel with post-traumatic stress disorder (PTSD). Method : A systematic review was undertaken according to Cochrane Collaboration Guidelines. The primary outcome measure was reduction in PTSD symptoms and the secondary outcome dropout. Results : Twenty-four studies with 2386 participants were included. Evidence demonstrated that CBT with a trauma focus (CBT-TF) was associated with the largest evidence of effect when compared to waitlist/usual care in reducing PTSD symptoms post treatment (10 studies; n = 524; SMD −1.22, −1.78 to −0.66). Group CBT-TF was less effective when compared to individual CBT-TF at reducing PTSD symptoms post treatment (1 study; n = 268; SMD −0.35, −0.11 to −0.59). Eye Movement Desensitization and Reprocessing (EMDR) therapy was not effective when compared to waitlist/usual care at reducing PTSD symptoms post treatment (4 studies; n = 92; SMD −0.83, −1.75 to 0.10). There was evidence of greater dropout from CBT-TF therapies compared to waitlist and Present Centred Therapy. Conclusions : The evidence, albeit limited, supports individual CBT-TF as the first-line psychological treatment of PTSD in active duty and ex-serving personnel. There is evidence for Group CBT-TF, but this is not as strong as for individual CBT-TF. EMDR cannot be recommended as a first line therapy at present and urgently requires further evaluation. Lower effect sizes than for other populations with PTSD and high levels of drop-out suggest that CBT-TF in its current formats is not optimally acceptable and further research is required to develop and evaluate more effective treatments for PTSD and complex PTSD in active duty and ex-serving military personnel. HIGHLIGHTS: PTSD is a common psychiatric condition amongst active duty and ex-serving military personnel. Evidence supports individual CBT-TF as the first-line psychological treatment of PTSD in active duty and ex-serving personnel. High levels of drop-out suggest that CBT-TF in its current formats of delivery is not optimally acceptable to active duty and ex-serving military personnel. EMDR currently cannot be recommended as a first line therapy for active duty and ex-serving military personnel and further evaluation is urgently required.